The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/mnras/stw2597
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the environment around five ultracool dwarfs via the radio domain

Abstract: We present the results of a series of short radio observations of six ultracool dwarfs made using the upgraded VLA in S (2-4GHz) and C (4-7GHz) bands. LSR J1835+3259 exhibits a 100 percent right-hand circularly polarised burst which shows intense narrowband features with a fast negative frequency drift of about −30 MHz s −1 . They are superimposed on a fainter broadband emission feature with a total duration of about 20 minutes, bandwidth of about 1 GHz, centred at about 3.5 GHz, and a slow positive frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 92 publications
2
24
0
Order By: Relevance
“…2MASS J00361617+1821104 (hereafter 2M 0036+18): this is an L3.5 dwarf at a distance of 8.74 ± 0.01 pc (Gaia Collaboration et al 2018). It is a well-studied object at radio frequencies, having been detected, for example, by Berger (2002); Berger et al (2005), and Metodieva et al (2017).…”
Section: Target Selection and Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…2MASS J00361617+1821104 (hereafter 2M 0036+18): this is an L3.5 dwarf at a distance of 8.74 ± 0.01 pc (Gaia Collaboration et al 2018). It is a well-studied object at radio frequencies, having been detected, for example, by Berger (2002); Berger et al (2005), and Metodieva et al (2017).…”
Section: Target Selection and Descriptionmentioning
confidence: 99%
“…We found that the modelled flux densities depend weakly on the viewing angle θ between the line of sight and the magnetic field, for values between 10 − 80 • . Therefore, to simplify the modelling procedure, we chose to keep θ fixed at 25 • , within the range of acceptable values reported by Metodieva et al (2017), ignoring the sense of polarization. We empirically determined the spectral turnover frequency by running a Markov Chain Monte Carlo sampler, from the emcee package (Foreman-Mackey et al 2013), to fit a broken power law of the form…”
Section: Coronal Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The auroral radio emission gives a snapshot of the stellar magnetic field topology at the epoch of its detection, and its modelling has been already used as a method to describe the field topology of UCD magnetospheres (Metodieva et al 2017). …”
Section: The Magnetosphere Of Tvlm 513-46546mentioning
confidence: 99%